2016
DOI: 10.1016/j.ijid.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of age and sex in determining antibiotic resistance in febrile urinary tract infections

Abstract: Age is not a considerable factor in determining the antibiotic resistance in febrile UTIs. Ciprofloxacin should be withheld from both sexes until culture results indicate its use. Second- or third-generation cephalosporins such as cefoxitin and cefotaxime can be used empirically only in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
6
18
0
2
Order By: Relevance
“…Antibacterial resistance micro-organisms limit and complicate treatment which is difficult to overcome due to multidrug resistant properties. The outcome of this study showed a high prevalence of Escherichia coli from several sources of clinical samples associated with multiple resistance genes.In a previous investigation, sex-dependent antibiotic resistance was established (Ben-Ami et al, 2009) while in a recent study, age was not a substantial issue in defining the antibiotic resistance but gender plays a vital role in the sensitivity (Lee et al, 2016). This study revealed that no antibiotic resistance significant variance in between the males and females (P >.05) which is also in agreement with a previous study by Ghadiri (Ghadiri et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Antibacterial resistance micro-organisms limit and complicate treatment which is difficult to overcome due to multidrug resistant properties. The outcome of this study showed a high prevalence of Escherichia coli from several sources of clinical samples associated with multiple resistance genes.In a previous investigation, sex-dependent antibiotic resistance was established (Ben-Ami et al, 2009) while in a recent study, age was not a substantial issue in defining the antibiotic resistance but gender plays a vital role in the sensitivity (Lee et al, 2016). This study revealed that no antibiotic resistance significant variance in between the males and females (P >.05) which is also in agreement with a previous study by Ghadiri (Ghadiri et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…and most (47.7%) resistant gene was isolated from pus swabs(Okoche et al, 2015). More than 80% of the urinary tract infections (UTI) while female febrile UTIs 86.3% and male febrile UTIs 78.5% are due to E. coli(Lee et al, 2016). Misappropriation of antibiotic is liable for the higher incidence of antibiotic resistance among bacteria(Neupane et al, 2016).…”
mentioning
confidence: 99%
“…Unfortunately, in our analysis, SA strains isolated from older patients demonstrated significantly increased TMP/SXT resistance, limiting its usefulness in the treatment of patients aged ≥75 years. Lee et al showed strains isolated from patients with febrile urinary tract infections demonstrating very high resistance to TMP/SXT, no metter how old the patients were [ 23 ]. According to a study by Leistevuo et al, TMP/SXT (or trimethoprim alone) was most frequently prescribed antimicrobial medicine to aged ≥85 years females with urinary tract infections (37%) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Lee et al, the susceptibility of gram-negative bacteria to ciprofloxacin was much higher in patients less than 20 years old than in patients more than 20 years old. The reason for this observation may be the lower exposure to fluoroquinolones in young individuals because these drugs are not recommended for use in those under 20 years old [ 17 ].…”
Section: Antimicrobial Susceptibility Pattern Of E Colimentioning
confidence: 99%
“…Catheter-associated UTIs have multiple confounding factors associated with emerging antimicrobial resistance, that is, hospital factors due to frequent hospitalization, foreign body bridges between the urinary bladder and the outside of the body, and frequent antibiotic exposure. A previous study conducted with outpatient UTIs showed that catheter-associated UTIs were more closely associated to exposure to antibiotics and exhibited a higher occurrence of infection caused by an atypical organism, such as Citrobacter species, Proteus mirabilis , Morganella morganii , Enterobacter species , and Pseudomonas aeruginosa rather than E. coli [ 17 ]. Those atypical organisms can harbor MDR determinant and can transfer the resistance determinants (e.g., AmpC gene) to E. coli (see Section 5 ).…”
Section: Complicated Utis and Mdr Gram-negative Bacteriamentioning
confidence: 99%